Apoptosis Inhibitor of Macrophage (CD5‐Like Antigen) in Healthy Dogs and Dogs With Acute Kidney Injury - William H. Whitehouse; Rodrigo Mohallem; Uma K. Aryal (Journal of Veterinary Internal Medicine)
ABSTRACT Background Apoptosis inhibitor of macrophage (AIM) is a fundamental mediator of recovery from acute kidney injury (AKI) in mice, but its role in AKI in dogs is unknown. Hypothesis/Objectives To detect and quantify AIM in serum and urine from both healthy dogs and dogs with AKI, and to determine if AIM is higher in dogs with AKI compared to healthy controls. Animals Eight dogs with International Renal Interest Society (IRIS) Grade II–V AKI and 10 healthy adult dogs. Methods Retrospective case–control study. Liquid chromatography‐mass spectrometry (LC–MS) based targeted proteomics was used to quantify AIM. AIM peak areas were compared between the AKI and healthy cohorts and correlated with selected markers of renal function. Results AIM was able to be quantified in the urine of 5/8 dogs with AKI and 1/10 healthy dogs. AIM was quantified in the serum of all dogs, and there was no difference in peak area between the two groups (AKI: median, 67 840 (range, 9797‐98 725); control: median, 79 072 (range, 46 400‐160 330); p = 0.274). In dogs with AKI, AIM was not correlated with serum creatinine, blood urea nitrogen, phosphorus, or potassium concentrations, urine specific gravity, or IRIS AKI grade. Conclusions and Clinical Importance AIM was predominantly detected in the urine of dogs with AKI and not in the urine of healthy dogs.